Experimental analysis of glued-in steel plates used as shear connectors in Timber-Concrete-Composites. (1st September 2018) - Otero-Chans, Dolores; Estévez-Cimadevila, Javier; Suárez-Riestra, Félix; Martín-Gutiérrez, Emilio
Graphical abstract: Highlights: Timber-concrete-composite connections using discrete steel meshes are investigated. Three different configurations using plates and reinforcing bars are studied. Effect of plate length on connection strength and stiffness is studied. Abstract: This paper describes experimental research into timber-concrete composite (TCC) connections made with discrete perforated steel plates glued in timber with epoxy adhesive. Continuous steel meshes have proven to be very strong and rigid elements in TCC structural members. This paper studies the strength and stiffness of these connectors when used in a discrete way, alone and in combination with reinforcing bars. Six types of connector were subjected to experimental tests, analysing two connection lengths and three configuration systems of the connector elements (in which bars are added longitudinally or transversally). The experimental results show that the connections made with discrete steel meshes are very strong and rigid, and that it is possible to design them for ductile failure. Comparison of the results for plates of different lengths indicates that failure occurs in the longest connections in the wood at lower average shear stresses. No significant behavioural differences were detected between connectors made only of plate and those that were reinforced with additional bars. The high slip moduli values indicate that it would be possible to design structural elements with a composite action close to 100% using this type of connection.